Identification of DLEU2 as biomarker based on lncRNA-Mediated ceRNA network in rupture of intracranial aneurysm: DLEU2: A lncRNA biomarker in intracranial aneurysm rupture - Gao, Yanlei; Yu, Tao (Cellular and Molecular Biology, 2024)
Intracranial aneurysms (IA) is a potentially devastating clinical problem that may cause lethal subarachnoid hemorrhage upon rupture, but the molecular mechanisms remain further elucidated. Our goal in this work was to build the lncRNA-mediated ceRNA network in IS and explore the associated pathways and functions. The deep transcriptome sequencing dataset profile of rupture of IA and normal tissues (SRP150595) was obtained from NCBI database. To determine which genes were differently expressed, weighted gene co-expression network analysis and other integrated bioinformatics techniques were used (DEGs). The action mechanism and associated pathways of DEGs in IA were investigated using GO annotations and KEGG analysis. The Starbase database was used to build the ceRNA network. Vascular smooth muscle cells (VSMC) were used for the transwell assay and CCK-8. A total of 248 common differentially expressed-protein coding RNA and 76 DE-lncRNAs were obtained. Functional enrichment analysis indicated that the DEGs of IA are involved in pathways of inflammation and immune response. A lncRNAs-mediated ceRNA network including lncRNAs BASP1-AS1, DLEU2, LINC02035, LINC02363, MMP25-AS1, AC008771.1 was constructed. The biological behavior of VSMC was suppressed when DLEU2 was knocked down. In conclusion, a lncRNAs-mediated ceRNA network was constructed in IA based on the integrated bioinformatics analyses, in which DLEU2 was identified to be a novel and potential biomarker of IA.